G⇒(3x ₊ 2)²₋ (3x ₊ 2) (x ₊ 7) Dans chaque cas,calculer G en indiquant l'expression utilisée pour x⇒2,5 pour x⇒0 pour x⇒ ₋1
G = (3x + 2)² - (3x + 2) (x + 7)
G = 9x² + 12x + 4 - (3x² + 21x + 2x + 14)
G = 9x² + 12x + 4 - 3x² - 21x - 2x - 14
G = 9x² - 3x² + 12x - 21x - 2x + 4 - 14
G = 6x² - 11x - 10
Pour x = 2,5
G = 6x² - 11x - 10
G = 6 * 2,5² - 11 * 2,5 - 10
G = 6 * 6,25 + 27,5 - 10
G = 37,5 + 27,5 - 10
G = 55
Pour x = 0
G = 6x² - 11x - 10
G = 6 * 0² - 11 * 0 - 10
G = - 10
Pour x = - 1
G = 6x² - 11x - 10
G = 6 * 1² - 11 * 1 - 10
G = 6 - 11 - 10
G = - 15